2018
DOI: 10.1108/ijotb-03-2018-0025
|View full text |Cite
|
Sign up to set email alerts
|

Impact of health sector reforms on hospital productivity in Turkey

Abstract: Purpose Turkish Ministry of Health (MoH) has Health Transformation Program (HTP). The purpose of this program has been to modify the structure of the current system in order to enhance health system productivity, quality, and access in the Turkish health system. The paper aims to discuss these issues. Design/methodology/approach To measure the productivity, a data envelopment analysis-based Malmquist index approach was employed. Findings Results showed that the overall HTP have had a considerable positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 28 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…Studies in Turkey showed that HTP implementation in this country was successful and had a significant impact on hospitals’ efficiency and productivity. Mollahaliloglu concluded that hospital efficiency and productivity increased following HTP implementation [ 35 ]. The Sahin study has shown that Turkish public hospitals’ productivity improved from 2005 to 2008 [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in Turkey showed that HTP implementation in this country was successful and had a significant impact on hospitals’ efficiency and productivity. Mollahaliloglu concluded that hospital efficiency and productivity increased following HTP implementation [ 35 ]. The Sahin study has shown that Turkish public hospitals’ productivity improved from 2005 to 2008 [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, it is worth mentioning that in recent years many countries have implemented reforms marked by financial restructuring of their health systems (increasing concentration by allowing mergers of hospitals) to enhance productivity, solve equity problems and facilitate access to health services. Therefore, it is becoming increasingly common to find studies that use frontier techniques such as DEA or MPI to evaluate the impact of those reforms [52,56,[71][72][73]. Therefore, the methodology proposed in this study could also be applied for this purpose in the event that the Panamanian authorities decide to implement some specific reforms regarding the structure of its health system in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…It was also found that the TFP average was below 1 in 2014-2015 and above 1 in other periods. Mollahaliloglu et al (2018) in the study conducted with MPI analysis to examine the results of the health transformation program in Turkey; the results were found to have a positive effect on hospital efficiency. The years 2001-2009 were researched.…”
Section: Discussionmentioning
confidence: 99%